Blood immune cell biomarkers in lung cancer. (9th November 2018) - Riemann, D.; Cwikowski, M.; Turzer, S.; Giese, T.; Grallert, M.; Schütte, W.; Seliger, B.
Summary: Characterization of host immune cell parameters prior to treatment is expected to identify biomarkers predictive of clinical outcome as well as to elucidate why some patients fail to respond to immunotherapy. We monitored blood immune cells from 58 patients with non‐small‐ cell lung cancer (NSCLC) undergoing surgery of the primary tumor and from 50 age‐matched healthy volunteers. Complete leukocyte blood count, the number of circulating dendritic cells (DC), HLA‐DR low monocytes and several lymphocytic subpopulations were determined by eight‐color flow cytometry. Furthermore, the prognostic value of the immune cell parameters investigated was evaluated by patients' survival analysis. Compared to the control group, blood of NSCLC patients contained more neutrophils resulting in a higher neutrophil‐to‐lymphocyte ratio (NLR), but a lower number of blood DC, in particular of plasmacytoid DC (pDC), natural killer (NK) cells and naive CD4 + and CD8 + T cells. Furthermore, a higher frequency of CD4 + regulatory T cells (Treg) and HLA‐DR low monocytes was detected, and smoking had a significant impact on these values. HLA‐DR low monocytes were positively correlated to the number of neutrophils, monocytes and NLR, but negatively associated with the number of pDC and naive CD4 + T cells. The frequency of Treg, HLA‐DR low monocytes and naive CD4 + and CD8 + T cells as well as the ratios of CD4/HLA‐DR low monocytes and HLA‐DR low monocytes/pDC correlated with patient's overall survival. Next to Treg, HLA‐DR low monocytes and naive T cells represent prognostic markers for NSCLC patients and might be useful for monitoring of patients' responses to immunotherapies in future studies. Abstract : Using 8‐color flow cytometry und survival analysis, we show that the frequency of Treg, HLA‐DRlow monocytes and naïve CD4+ and CD8+ T cells as well as the ratios of CD4/HLA‐DRlow monocytes and HLA‐DRlow monocytes/PDC correlated with patient's overall survival. Next to Treg, HLA‐DRlow monocytes and naïve T cells represent prognostic markers for NSCLC patients and might be useful for monitoring of patient's responses to immunotherapies in future studies.